(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
The governance of the European Union (EU) through treaties and without an adequate structure of its institutions is complex, inefficient, lacks transparency and legitimacy, and is difficult to understand for citizens. Furthermore, there is no clear separation of powers in the EU and, while a succession of treaties has gradually increased the powers of the European Parliament, its ability to influence and develop policies remains limited and subordinate to the European Commission and Council. A serious problem for the EU is that its citizens usually know little about their elected representatives and lack information about how political decisions are made. The large number of actors and the complexity of institutional links, the lack of transparency in consensus decision-making within the Council, and the drafting of laws and regulations by unelected technocrats instead of popularly elected representatives, are elements that call into question the democratic quality of the EU and erode its institutions. To overcome the important problems that plague the EU democratic system, it will be necessary to build a common European project where the different powers are strictly separated and citizens have direct participation in decision-making. To this end, a Citizens’ Convention led by the Federal Alliance of European Federalists (FAEF) was held between October 2021 and April 2022 to replace the EU treaties with a Constitution and establish the Federated States of Europe. The work of the more than 70 members who participated in the Citizen Convention was captured in a Constitution with ten articles that establish the necessary government structures of the Federation and the citizens’ rights and duties.